2015
DOI: 10.3389/fphys.2015.00243
|View full text |Cite
|
Sign up to set email alerts
|

The new nitric oxide donor cyclohexane nitrate induces vasorelaxation, hypotension, and antihypertensive effects via NO/cGMP/PKG pathway

Abstract: We investigated the cardiovascular effects induced by the nitric oxide donor Cyclohexane Nitrate (HEX). Vasodilatation, NO release and the effects of acute or sub-chronic treatment with HEX on cardiovascular parameters were evaluated. HEX induced endothelium-independent vasodilatation (Maximum effect [efficacy, ME] = 100.4 ± 4.1%; potency [pD2] = 5.1 ± 0.1). Relaxation was attenuated by scavenging nitric oxide (ME = 44.9 ± 9.4% vs. 100.4 ± 4.1%) or by inhibiting the soluble guanylyl cyclase (ME = 38.5 ± 9.7% v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The data showed that L-NAME considerably diminished the vasodilation resulting from Tsantan Sumtang treatment at the 0.9 and 1.2 mg/mL levels, signifying that NO plays a role in the vasorelaxation induced by Tsantan Sumtang, and the medicine improved the production of NO from L-arginine by endothelial nitric oxide synthase (eNOS) in the vascular endothelium and stimulated guanylate cyclase, thereby catalyzing the transformation of GTP to cGMP and reducing the internal Ca 2+ flow through cGMP-dependent protein kinase [12]. Thus, the pulmonary arteries were dilated by increasing the intake of Ca 2+ in the sarcoplasmic reticulum by Ca 2+ -ATPase or by directly leading to contractile protein dephosphorylation [29]. Furthermore, IMT, an inhibitor of cyclooxygenase (COX, a key PGI2 synthetase), had an even stronger influence at the same concentration levels, indicating that PGI2 was more likely to be involved in the vasorelaxation by Tsantan Sumtang and to play a more important role.…”
Section: Discussionmentioning
confidence: 99%
“…The data showed that L-NAME considerably diminished the vasodilation resulting from Tsantan Sumtang treatment at the 0.9 and 1.2 mg/mL levels, signifying that NO plays a role in the vasorelaxation induced by Tsantan Sumtang, and the medicine improved the production of NO from L-arginine by endothelial nitric oxide synthase (eNOS) in the vascular endothelium and stimulated guanylate cyclase, thereby catalyzing the transformation of GTP to cGMP and reducing the internal Ca 2+ flow through cGMP-dependent protein kinase [12]. Thus, the pulmonary arteries were dilated by increasing the intake of Ca 2+ in the sarcoplasmic reticulum by Ca 2+ -ATPase or by directly leading to contractile protein dephosphorylation [29]. Furthermore, IMT, an inhibitor of cyclooxygenase (COX, a key PGI2 synthetase), had an even stronger influence at the same concentration levels, indicating that PGI2 was more likely to be involved in the vasorelaxation by Tsantan Sumtang and to play a more important role.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the vascular effect of this compound could be attributed to NO/cGMP mechanism. Other studies seeking for new compounds have also documented that the NO/cGMP pathway is involved in the hypotensive effect of those compounds ( França-Silva et al, 2012a ; Dantas et al, 2014 ; Mendes-Júnior et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another NO donor, cyclohexane nitrate (HEX), was able to induce vasodilatation through the NO/cGMP/PKG pathway and activation of ATP-dependent K + channels, thus reducing blood pressure and heart rate in hypertensive rats. 65…”
Section: Nitric Oxide Dysfunctional Pathways In CV Diseasesmentioning
confidence: 99%
“…64 Another NO donor, cyclohexane nitrate (HEX), was able to induce vasodilatation through the NO/cGMP/PKG pathway and activation of ATP-dependent K þ channels, thus reducing blood pressure and heart rate in hypertensive rats. 65 Further evidence suggested that, in hypertensive conditions, S-Nitroso-N-acetyl-DL-penicillamine (SNAP) decreased the expression of inhibitory guanine nucleotide regulatory protein a (Gia) proteins and hyperproliferation of VSMC by a cGMPindependent mechanism. The decreased Gia proteins, induced by NO, occurred through its ability to reduce oxidative stress and promote growth factor receptors/mitogen-activated protein kinase signaling.…”
Section: Nitric Oxide and Hypertensionmentioning
confidence: 99%